2008
DOI: 10.1029/2007jf000860
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “High‐angle wave instability and emergent shoreline shapes: 1. Modeling of sand waves, flying spits, and capes” by Andrew D. Ashton and A. Brad Murray

Abstract: [1] Ashton and Murray [2006a, 2006b] (henceforth referred to as AM06) showed that coastal evolution can be strongly affected by wave angle when it is formulated in terms of deepwater wave quantities. Most alongshore sediment transport formulae (i.e., CERC formulation) are expressed in terms of the breaking-wave height and the breaking-wave angle. In such formulae, if the breakingwave height is held constant, the alongshore sediment transport is maximized when waves are breaking at an angle of 45°. For breakin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…As a first approximation, Ortega-Sánchez et al (2008b) applied the model developed by Ashton and Murray (2006a,b) and found good general agreement between the large-scale features of Carchuna Beach and the results obtained using the Ashton and Murray (2006a) model. According to this model, instabilities and rhythmic features tend to appear on coastlines where the waves impinge with an obliquity greater than 45°with respect to the shore-normal orientation.…”
Section: The Shape Of the Hornsmentioning
confidence: 58%
See 1 more Smart Citation
“…As a first approximation, Ortega-Sánchez et al (2008b) applied the model developed by Ashton and Murray (2006a,b) and found good general agreement between the large-scale features of Carchuna Beach and the results obtained using the Ashton and Murray (2006a) model. According to this model, instabilities and rhythmic features tend to appear on coastlines where the waves impinge with an obliquity greater than 45°with respect to the shore-normal orientation.…”
Section: The Shape Of the Hornsmentioning
confidence: 58%
“…Nevertheless, there were some aspects that were not reproduced by the model: 1) the protruding horns do not have a symmetric shape, 2) there is a general alongshore variation in the shape of the features, and 3) the relative orientation of the shoreline changes between features. Ortega-Sánchez et al (2008b) concluded that nearshore wave energy modulation should be considered to fully explain the morphology of Carchuna Beach.…”
Section: The Shape Of the Hornsmentioning
confidence: 97%
“…The beach presents a complex shoreline morphology, characterized by four large scale irregularly spaced cuspate features limited by seaward protruding horns and a peculiar bathymetry comprised of fluvial valleys to the west of the Cape. The beach experiences the co‐existence of a number of physical processes (wave refraction patterns over submarine fluvial canyons, progressive or quasi‐stationary edge waves trapped between the horns, offshore high angle waves instabilities, wind‐wave coupling) that may define its morphology [ Ortega‐Sánchez et al , 2003, 2008; Quevedo et al , 2008].…”
Section: Field Site and Physical Processesmentioning
confidence: 99%
“… Ashton and Murray [2006b] present a methodology for more rigorously analyzing and characterizing a wave climate, introducing a stability parameter, Γ. Approximate values of this stability parameter can be computed using wave energy roses such as those presented in the comment by Ortega‐Sánchez et al [2008], and its computation should be more straightforward than approximations of the model parameter H .…”
mentioning
confidence: 99%
“…A and U are model-specific parameters used to determine the wave climate in the numerical experiments [e.g., Ashton and Murray, 2006a, Figure 8], and should not be directly related to a natural wave climate with the expectation of a quantitatively accurate comparison. Ashton and Murray [2006b] present a methodology for more rigorously analyzing and characterizing a wave climate, introducing a stability parameter, G. Approximate values of this stability parameter can be computed using wave energy roses such as those presented in the comment by Ortega-Sánchez et al [2008], and its computation should be more straightforward than approximations of the model parameter H.…”
mentioning
confidence: 99%